2020
DOI: 10.1002/jts.22539
|View full text |Cite
|
Sign up to set email alerts
|

Minority Participation in Randomized Controlled Trials for Prolonged Exposure Therapy: A Systematic Review of the Literature

Abstract: Per the most recent census, non‐Latinx White individuals comprise the majority of the U.S. population (76.6%); Latinx individuals make up 18.3% of the total U.S. population, followed by African Americans (13.4%) and Asians (5.9%). Given the high prevalence rates of posttraumatic stress disorder (PTSD) observed across many ethnoracial minority groups in the United States, the fact that PTSD presentation may vary across culture, and the National Institute of Health's mandates for the inclusion of women and minor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 61 publications
0
34
0
Order By: Relevance
“… 6 8 Although several efficacious treatments exist for PTSD (eg, prolonged exposure 9 and cognitive processing therapy 10 ) existing treatment studies largely do not address the role of race or ethnicity. 11 Furthermore, evidence shows that treatment dropout rates are high among POC. 12 , 13 Thus, the development of treatments for racial trauma is sorely lacking.…”
Section: Introductionmentioning
confidence: 99%
“… 6 8 Although several efficacious treatments exist for PTSD (eg, prolonged exposure 9 and cognitive processing therapy 10 ) existing treatment studies largely do not address the role of race or ethnicity. 11 Furthermore, evidence shows that treatment dropout rates are high among POC. 12 , 13 Thus, the development of treatments for racial trauma is sorely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these efforts, literature reviews of ethnoracial minority representation in clinical trials for obsessive compulsive disorder (OCD; Williams et al, 2010), panic disorder (Mendoza et al, 2012), depression (Polo et al, 2019), posttraumatic stress disorder (PTSD; Grau et al, 2021), and Prolonged Exposure (PE) therapy for PTSD (Benuto et al, 2020) reveal that ethnoracial minority groups are largely underrepresented in the RCTs that comprise the evidence base for these treatments. Fewer than half of the RCTs for OCD, panic disorder, and depression even reported the ethnoracial characteristics of the samples (Mendoza et al, 2012; Polo et al, 2019; Williams et al, 2010), though there is evidence that reporting practices in clinical trials for depression have improved over time (Polo et al, 2019).…”
mentioning
confidence: 99%
“…Additionally, Marquez (2019) found that level of adherence to Latinx culture was a significant predictor of treatment acceptability for therapy. The results from these studies highlight the intricate interplay of cultural values with attitudes and beliefs about treatment and suggest that adherence to cultural factors might predict treatment acceptability, particularly considering that exposure-based treatments were developed in a non-Latinx context, and most studies have not included an adequate representation of Latinx participants (Benuto et al, 2020).…”
Section: Treatment Acceptabilitymentioning
confidence: 99%